2019
DOI: 10.1021/acs.jpclett.9b01083
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Assisted Suppression of Surface Trap States and Enhanced Band-Edge Emission in a Bare CdTe Quantum Dot

Abstract: Colloidal quantum dots have emerged as a versatile photoluminescent and optoelectronic material. Limitations like fluorescence intermittency, non-radiative Auger recombination and surface traps are commonly addressed by growing a wide-bandgap shell. However, the shell isolates the excitonic wave function and reduces its interaction with the external environment necessary for different applications. Furthermore, their long emission lifetime hinders their use in high-speed optoelectronics.Here, we demonstrate a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(62 reference statements)
0
13
0
1
Order By: Relevance
“…Despite this wealth of information, there is less understanding of their influence in optical cavities, as well as the interplay with intrinsic excitons. [34] Here, we demonstrate for the first time that the carrier recombination process in QDs is significantly modified by a plasmonic nanocavity, resulting in dominant trap state emission under two-photon excitation. We use a 'nanoparticle-on-mirror' (NPoM) geometry [35], built of individual Au nanoparticles above a Au film with QDs sandwiched between the metallic surfaces (Fig.…”
mentioning
confidence: 81%
“…Despite this wealth of information, there is less understanding of their influence in optical cavities, as well as the interplay with intrinsic excitons. [34] Here, we demonstrate for the first time that the carrier recombination process in QDs is significantly modified by a plasmonic nanocavity, resulting in dominant trap state emission under two-photon excitation. We use a 'nanoparticle-on-mirror' (NPoM) geometry [35], built of individual Au nanoparticles above a Au film with QDs sandwiched between the metallic surfaces (Fig.…”
mentioning
confidence: 81%
“…Flatae et al studied the phenomena of QDs CdTe based on plasmon coupling and investigated its properties. They concluded that plasmon coupling on the QDs could increase the optical properties in different applications of electronic and optical devices . They gained about 99% of the surface defect‐state emission from a trap‐rich QD.…”
Section: Mechanism Of Plasmonic‐assisted Devicesmentioning
confidence: 99%
“…They concluded that plasmon coupling on the QDs could increase the optical properties in different applications of electronic and optical devices. [131] They gained about 99% of the surface defect-state emission from a trap-rich QD. Furthermore, two critical parameters and edge state excitonic and bi-excitonic emission rates are seen to be increased by ≈1460and 613-fold, respectively.…”
Section: Others Applicationsmentioning
confidence: 99%
“…Для КТ, обладающих дефектной люминесценцией ( " trap state luminescence"), эффекты плекситонного взаимодействия практически не изучены. В работах [14][15][16][17] продемонстрировано управление излучением ловушечных состояний одиночных КТ и их ансамблей за счет взаимодействия с плазмонными НЧ. Найдено усиление экситонной люминесценции за счет подавления дефектной люминесценции.…”
Section: Introductionunclassified